The Relationship of Blood Eosinophils Levels with Degree of Exacerbation in COPD Patient at Usu General Hospital - Deneuve, Olivia Monica; Pradana, Andika; Tarigan, Amira P. (Journal of Society Medicine, 2024)
Introduction: During acute exacerbations of chronic obstructive pulmonary disease (COPD), blood eosinophil count has the potential to predict treatment response. Nevertheless, there hasn’t been enough research done to determine whether blood eosinophil numbers in a stable state can forecast an eosinophilic exacerbation. Methods: This study was a retrospective cohort analysis performed July-August 2022 to July-August 2023. Subject were 44 COPD patients who were treated at the outpatient clinic. Blood samples measured blood eosinophil levels. We determined an absolute cut-off point for blood eosinophil count at stable COPD in order to identify the rate of exacerbation. Results: Based on the Kruskal-Walli’s test, there was a significant relationship between blood eosinophils and the level of exacerbations in COPD patients (p value = 0.003). Conclusion: We established a relationship between the rate of exacerbation and blood eosinophil counts during stable COPD. The rate of exacerbation and eosinophil counts showed a strong positive relationship. Our findings should be confirmed by prospective and further research in different populations.